Edukasi pengenalan bentuk dan logo obat pada siswa-siswi SMA Unggulan Haf-Sa Zainul Hasan BPPT - Latifah, Luluk; Adianto, Arda; Salsa, Sandryna Aulia; Fanani, Filzah (P3HKI - Universitas Muhammadiyah Parepare, 2024)
Pharmaceutical preparations, such as medicines, traditional remedies, and cosmetics, play a vital role in maintaining health. However, many adolescents engage in self-medication without adequate knowledge, including recognizing logos and the forms of medicines on packaging. This lack of literacy increases the risk of incorrect drug use and harmful side effects. Studies indicate that most adolescents rely on information from advertisements or peers and frequently purchase medications without a doctor's prescription, which can jeopardize their health. Education on drug logos and forms is crucial, especially for high school students, to promote rational and responsible drug use. This program aims to enhance students' literacy regarding drug types, how to read information on packaging, and the importance of recognizing visual differences between drugs. The education was conducted through an interactive seminar at SMAU Haf-Sa Zainul Hasan BPPT using a visual approach, introducing various drug forms and logos, as well as how to review information on drug packaging. The results showed a significant improvement in students' understanding. Before the education, only 50% of the students were knowledgeable about drug logos and forms. After the program, 100% of the students demonstrated comprehension, as evidenced by the post-test results. This program successfully highlighted the importance of health education in fostering rational understanding of drug use. Additionally, students are expected to become agents of change by disseminating this knowledge to their families and communities.